2018
DOI: 10.1002/jsid.681
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the hole transport layers on the performance of blue and color tunable quantum dot light‐emitting diodes

Abstract: The performance of the blue quantum dot light‐emitting diodes (QLEDs) is largely affected by the hole transport layers (HTLs). As a consequence of the deep valance band level of blue quantum dots (QDs), hole injection is relatively difficult in blue QLEDs. To favor the hole injection, HTLs with high hole mobility and deep‐lying highest occupied molecular orbital level are desired. In this work, various HTLs and their influence on the performance of blue QLEDs are demonstrated. Devices with poly(N‐vinylcarbazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…However, the external quantum efficiency (EQE) of Cd-based QLEDs is vulnerable to offset between the highest occupied molecular orbital (HOMO) level of TFB and QDs hole level which is particularly high for ZnS-coated QDs . As a result, device performance is very sensitive to the electron accumulation in the QDs layer that leads to a drop of radiative recombination efficiency as a result of Auger processes . Accumulated electrons tend also to leak into the adjacent TFB layer and cause electrochemical reactions deteriorating hole transport in TFB which is essential for device stability …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…However, the external quantum efficiency (EQE) of Cd-based QLEDs is vulnerable to offset between the highest occupied molecular orbital (HOMO) level of TFB and QDs hole level which is particularly high for ZnS-coated QDs . As a result, device performance is very sensitive to the electron accumulation in the QDs layer that leads to a drop of radiative recombination efficiency as a result of Auger processes . Accumulated electrons tend also to leak into the adjacent TFB layer and cause electrochemical reactions deteriorating hole transport in TFB which is essential for device stability …”
Section: Resultssupporting
confidence: 81%
“…22 As a result, device performance is very sensitive to the electron accumulation in the QDs layer that leads to a drop of radiative recombination efficiency as a result of Auger processes. 23 Accumulated electrons tend also to leak into the adjacent TFB layer and cause electrochemical reactions deteriorating hole transport in TFB which is essential for device stability. 24 For this reason, it is important to provide a strategy either to minimize the hole injection barrier or to reduce electron injection.…”
Section: ■ Introductionmentioning
confidence: 99%
“…, interfacial recombination between organic and inorganic layer due to high injection barrier) that is originated from the recombination transition at the interface between trap states in the emissive layer and BCBP of HTL. 34–37 The J–V–L graph and the luminance pixel photo of the device with Sample-B emissive layer shown in Fig. 5(b) exhibit the turn-on voltage as around 8.2 V and have luminance up to 133.49 cd m −2 .…”
Section: Resultsmentioning
confidence: 99%
“…Using this approach, we have obtained a LT50 of 864,000 h (for a L 0 of 100 cd m –2 ) for red QDLEDs using a conventional core/shell QD emitter while also increasing the EQE to 11.1% compared to a device utilizing CBP alone as the HTL. Although there have been several reports of bilayer stepwise HTLs that demonstrate improvements in QDLED performance, ,,, we have found that a three-layer CHTL utilizing CBP, tris­(4-carbazoyl-9-ylphenyl)­amine (TCTA), and N , N ′-bis­(naphthalen-1-yl)- N , N ′-bis­(phenyl)­benzidine (NPB) allows for fine control over hole accumulation and electron–hole recombination in QDLEDs. To the best of our knowledge, this represents the longest LT50 for QDLEDs utilizing conventional core/shell QDs, suggesting that further stability enhancements may be possible if graded core/shell QDs are used in this QDLED architecture.…”
Section: Introductionmentioning
confidence: 99%